Measuring Generation Z’s Purchasing Decisions on Fashion Products on TikTok Live Streaming - Tri Wahyu Apriyani; Hesti Respatiningsih; Dewi Shanti Nugrahani (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyze the influence of content marketing and live streaming on purchasing decisions for fashion products among Generation Z users of the TikTok platform. In the era of digitalization and social media dominance, TikTok has emerged as one of the most influential platforms shaping consumer behavior, particularly for the younger generation. The research adopts an associative quantitative approach using a questionnaire survey distributed to 102 respondents who actively use TikTok for fashion-related content. The collected data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4 to test the hypothesized relationships between variables. The results indicate that both content marketing and live streaming significantly and positively affect purchasing decisions. The path coefficients of 0.361 for content marketing and 0.521 for live streaming demonstrate their substantial contribution. Furthermore, the research model yields an R-squared value of 0.640, suggesting that these two independent variables collectively explain 64% of the variance in purchasing decisions among Generation Z. In addition, the validity and reliability tests confirm that all constructs fulfill the eligibility criteria, reinforcing the robustness of the measurement model. These findings emphasize that content-based marketing strategies, when designed to be engaging, interactive, and visually appealing, are highly effective in fostering consumer interest and driving purchase intention. Live streaming, in particular, serves as a powerful marketing tool by offering real-time interaction, product demonstration, and a sense of authenticity that resonates strongly with Generation Z’s consumption patterns. The implications of this research highlight the strategic importance for fashion brands to optimize their digital marketing practices by integrating creative content marketing and live streaming features on TikTok.